2005
DOI: 10.1093/jac/dki347
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of high-level aminoglycoside-resistant enterococci isolated from patients in a university hospital in southern Italy

Abstract: The spread of the aac(6')-Ie-aph(2'')-Ia gene was responsible for high-level resistance to gentamicin and amikacin among enterococci isolated from patients in our geographical area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 26 publications
10
48
0
3
Order By: Relevance
“…This finding is a cause of concern, because it may indicate a major resistance problem in our hospitals in the near future. However, the resistance to gentamycin in high levels is of more importance than the resistance in high levels to streptomycin as HLR-GE predicts resistance to all other aminoglycosides, except streptomycin (22,25). Similar resistance rates of HLAR have been reported in Cuba by Quiñones et al (20) and in Peru by Kaçmaz & Aksoy (14).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This finding is a cause of concern, because it may indicate a major resistance problem in our hospitals in the near future. However, the resistance to gentamycin in high levels is of more importance than the resistance in high levels to streptomycin as HLR-GE predicts resistance to all other aminoglycosides, except streptomycin (22,25). Similar resistance rates of HLAR have been reported in Cuba by Quiñones et al (20) and in Peru by Kaçmaz & Aksoy (14).…”
Section: Discussionsupporting
confidence: 62%
“…Bactericidal antimicrobial activity, necessary for the treatment of enterococcal infections, is usually obtained by the synergistic combination of a cell-wall active agent, such as a β-lactams or a glycopeptide, with an aminoglycoside, such as gentamicin or streptomycin (3,25). Several studies have shown increasing resistance of enterococci to antimicrobial agents such as β-lactams, high-level aminoglycosides and more recently to glycopeptides (11,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…It is the most prevalent form of acquired gentamicin resistance in both species and associated with homologues of transposon Tn4001/Tn5281 flanked by two copies of IS256 and most probably originating from staphylococci (Casetta et al, 1998;Hallgren et al, 2003;Saeedi et al, 2004). Gentamicin resistance may also be encoded by other determinants such as aac(6')-Ii, aph(2")-Ie, and ant(6)-Ia (Jackson et al, 2004;Jackson et al, 2005;Zarrilli et al, 2005;Mahbub et al, 2005). High-level streptomycin resistance is encoded by the aadE gene which is an integral part of a multiresistance gene cluster aadE-sat4-aphA encoding streptomycin-streptothricin-kanamycin resistance.…”
Section: Aminoglycoside Resistancementioning
confidence: 99%
“…Some past studies have also indicated that E. faecium is the main species. In Italy, from the total HLGR isolates, 52% were E. faecium and 44% were reported as E. faecalis (24). In South Korea, 70% of HLGR isolates belonged to E. faecium (20).…”
Section: Discussionmentioning
confidence: 98%
“…faecalis is a pathogen with high pathogenesis, E. faecium due to its high potential in resistance against antibiotics, shows a high percentage of resistance to various antibiotics (24).…”
Section: Discussionmentioning
confidence: 99%